Association between HIV replication and serum leptin levels: an observational study of a cohort of HIV-1-infected South African women. - Azzoni, Livio; Crowther, Nigel J; Firnhaber, Cynthia; Foulkes, Andrea S; Yin, Xiangfan; Glencross, Deborah; Gross, Robert; Kaplan, Mitch D; Papasavvas, Emmanouil; Schulze, Doreen; Stevens, Wendy; van der Merwe, Tessa; et al. (Journal of the International AIDS Society, 2010)
Advanced HIV infection can result in lipoatrophy and wasting, even in the absence of ongoing opportunistic infections, suggesting that HIV may directly affect adipose tissue amount and distribution.
Keywords: Adult; Body Fat Distribution; Cross-Sectional Studies; Female; Glucose; HIV Infections; HIV-1; Humans; Leptin; Lipid Metabolism; South Africa; Viral Load